Hak Untuk Dilupakan Sebagai Implementasi Perlindungan Hukum Korban Cyberbullying (Studi Komparatif Indonesia dengan Korea Selatan) - Zahrani Salsabila; Aji Lukman Ibrahim (Fakultas Hukum Universitas Udayana, 2023)
This study aims to determine legal policies regarding cyberbullying in Indonesia dan South Korea, forms of legal protection, fulfillment of the right to be forgotten and so that Indonesia can have legal arguments that side with victims as a form of protection for victims of cyberbullying. This normative juridical law research is complemented by interviews and uses comparative, statutory, and conceptual approaches. The results of this study indicate that Indonesia has not been able to exercise the right to be forgotten in dealing with cyberbullying because there needs to be a precise mechanism in its legal policies. In addition, the lack of socialization regarding the implementation of the right to be forgotten for victims of cyberbullying causes low public awareness in reporting. Therefore, strategic steps are needed, such as issuing a Ministerial Regulation regarding the mechanism for deletion, the existence of a particular complaint, contacting persons, and conducting outreach and education to the public. Hence, they want to report on acts of cyberbullying.